An analysis of war trauma and refugee distress among Bosnian Muslim women : exploring social and personal healing in the aftermath - Murphy, Teri L (Department of Psychology, 2015)
This study is a narrative examination of the healing process in the aftermath of war trauma for nineteen Bosnian Muslim refugee women. Epistemologically informed by Feminist Standpoint Theory, a mixed methods approach of Grounded Theory, Narrative Analysis and Relational Voice Theory was used to show how recovery from multiple war trauma/violence has occurred only partially. By synthesizing theories of place identity, gender roles, and meaning making systems, the difficulties women face to integrate war and refugee experiences into social understanding is examined. Individuals in the study identified themselves as Bosnian women – culturally, nationally, ethnically, and religiously. Not only did war threaten those identifications, in some aspects, it fundamentally altered them. This paper argues that when the women were alienated from place attachments, their history and narratives were disrupted. They were dislocated from a literal space called “home” and they lost a sense of existential belonging and identity. Second, findings explicate how war and forced removals impacted familial and communal relationships. Women experienced relational losses through death and separation; they also lost the anchoring of their social identities. In exile, role expectations and demands radically shifted. Finally, narrative analysis demonstrates how traumatic events created an internal disorientation. Centralizing ethno-religious beliefs were shattered, leaving refugee women to face a crisis of meaning. Taken together, these findings elucidate how the radical discordance between pre/post-war place identification, role continuity, and cultural/religious belief systems is problematic and has made it difficult for Bosnian Muslim refugee women in the study to heal or to fully recover in the aftermath of war.